The Association of Broadband Internet Access and Telemedicine Utilization in rural Western Tennessee: an observational study - Jacob K. Quinton; Michael K. Ong; Sitaram Vangala; Anna Tetleton-Burns; Ashley Webb; Catherine Sarkisian; Alejandra Casillas; Preeti Kakani; Maria Han; Claude J. Pirtle (BMC, 2021)
Abstract Background Broadband access has been highlighted as a national policy priority to improve access to care in rural communities. Objective To determine whether broadband internet availability was associated with telemedicine adoption among a rural patient population in western Tennessee. Methods Observational study using electronic medical record data from March 13th, 2019 to March 13th, 2021. Multivariable logistic regression incorporating individual-level characteristics with broadband availability, income, educational attainment, and primary care physician supply at the zip code level, and rural status as determined at the county level. Setting Single health system in western Tennessee. Participants Adult patients with one or more in-person or remote encounter in a health system in western Tennessee and residing in western Tennessee between March 13th, 2019 and March 13th, 2021 (N = 54,688). Outcome measures Completion of one or more video encounters in the year following March 13th, 2020 (N = 3199; 7%). Our primary characteristic of interest was the proportion of residents in each zip code with access to the internet meeting the Federal Communications Commission definition of broadband access, adjusting for age, gender, race, income, educational attainment, insurance type, rural status, and primary care provider supply. Results Patients in a rural western Tennessee health system were predominantly white (79%), residing in rural zip codes (73%) with median household incomes ($52,085) less than state and national averages. Patients residing in a zip code where there is 80 to 100% broadband access compared to 0 to 20% were more likely in the year following March 13th, 2020 to have completed both telemedicine and in-person visits ([OR; 95% CI] 1.57; 1.29, 1.94), completed only telemedicine visits (2.26; 1.71, 2.97), less likely to have only completed in-person visits (0.81; 0.74, 0.89), but no more or less likely to have accessed no care (1.07; 0.97, 1.18). Discussion The availability of broadband internet was shown to be one of many factors associated with the utilization of telemedicine for a rural, working-class community after March 13th, 2020. Conclusions Access to broadband internet is a determinant of access to telemedicine for patients in rural communities and should be a priority for policymakers interested in improving health and access to care for rural patients.